Changes in the population aged over 75 of an urban general practice: implications for screening. Issue 6518 (15th February 1986) - Graham, H; Livesley, B
Abstract : In an urban group practice of six principals 545 (4.2%) of 13 100 patients were over 75 years of age. Although 54 of these patients died during one year, there were 72 "urban migrants" (42 removed from the district and were replaced by 30 new registrations) and 58 age transfers within the age-sex register. Although urban migrants who were aged over 75 and over 85 represented only a small percentage (0.6% and 0.1% respectively) of the total practice population, they accounted for 12.8% and 14.9% of their respective age groups. There may be delays of up to three months before such patients are routinely registered with new practices. Thus a potentially hidden and appreciably vulnerable section of the aged population who are likely to require crisis intervention has been identified. This may explain previous conflicting views about the value of health screening programmes in the elderly.